2015
DOI: 10.4236/wjns.2015.51007
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Changes in Alzheimer’s Disease Revealed by Diffusion Tensor Imaging with TBSS

Abstract: Alzheimer's disease (AD) is a progressive, neurodegenerative disorder characterized by impairments in multiple cognitive domains and it is hard to diagnose in early stage because it's not easy to recognize and develop slowly. In this study, we try to evaluate the difference of white matter between AD and health volunteers using diffusion tensor imaging (DTI) and try to provide some evidence for diagnose AD in early stage. Twelve elderly Chinese patients with AD and twelve healthy volunteers were recruited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
4
6
0
Order By: Relevance
“…Corticospinal tract was the disrupted projection fiber along with disruptions in forceps minor and forceps Disruptions in intrahemispheric and projection fiber tracts and white matter changes related to aging Decreased FA was spatially extensive in AD subjects; however, significant effects of decreased FA in comparison with MCI cohort were observed in voxels of specific fiber pathways; in particular, the inferior longitudinal fasciculus, forceps minor, forceps major, SLF, anterior thalamic radiation, IFOF, and corticospinal tract. These findings were consistent with existing literature (Chen et al, 2015;Mayo et al, 2019;Serra et al, 2010). Lower FA reflects extensive demyelination and light axonal packing as it would leave more intercellular water than dense packing (Feldman et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Corticospinal tract was the disrupted projection fiber along with disruptions in forceps minor and forceps Disruptions in intrahemispheric and projection fiber tracts and white matter changes related to aging Decreased FA was spatially extensive in AD subjects; however, significant effects of decreased FA in comparison with MCI cohort were observed in voxels of specific fiber pathways; in particular, the inferior longitudinal fasciculus, forceps minor, forceps major, SLF, anterior thalamic radiation, IFOF, and corticospinal tract. These findings were consistent with existing literature (Chen et al, 2015;Mayo et al, 2019;Serra et al, 2010). Lower FA reflects extensive demyelination and light axonal packing as it would leave more intercellular water than dense packing (Feldman et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The literature on topological disruptions along the AD continuum (Daianu et al, 2015; Lo et al, 2010; Rasero et al, 2017; Yan et al, 2018) supports the outcomes of our investigation, highlighting the potential of network efficiency as a cost‐effective, effective, and noninvasive biomarker for AD imaging. Moreover, we note that the distribution of ADPRs overlaps with the pathological progression frequently observed in the frontal, cingulate, precuneus, striatum, parietal, and lateral temporal cortices (Chen et al, 2023; Villemagne et al, 2018). The cerebral regions identified in our study closely align with confirmed sites of AD pathology deposition, strongly indicating that pathological deposition may contribute to deviations in local efficiency, ultimately resulting in cognitive decline.…”
Section: Discussionsupporting
confidence: 55%
“…Recent studies [16][17][18][19] suggest a direct role of white matter (WM) degeneration in AD/MCI pathogenesis. Similarly, diffusion tensor imaging (DTI)-based studies [17] show lower fractional anisotropy (FA) and higher mean diffusivity (MD) in MCI and AD patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%